Women and Religiosity in Orthodox Christianity - Merdjanova, Ina (Book collections on Project MUSE., 2021)
This volume engages women's lifeworlds, practices, and experiences in relation to Orthodox Christianity in multiple, varied localities, discussing both contemporary and pre-1989 developments. It critically engages the pluralist and changing character of Orthodox forms of institutional and social life in relation to gender by using feminist epistemologies and drawing on original ethnographic research.